Towards Understanding Relationships between Tension Property and Twinning Boundaries in Magnesium Alloy - Jianhui Bai; Pengfei Yang; Zhiyuan Yang; Qi Sun; Li Tan (Metals, 2021)
Although pre-induced <semantics>{10 <mover>12¯</mover>}</semantics> twins could strengthen magnesium and its alloys, the origin of such a strengthening phenomenon remains questionable. This is because twins can simultaneously change the size of grains and the texture features of the initial material. In the present work, the effect of pre-induced <semantics>{10<mover accent="true">1¯</mover>2}</semantics> twins on the tension property of an extruded magnesium alloy has been investigated through a combination of electron backscatter diffraction, transmission electron microscope, and mechanical tests. Samples with and without <semantics>{10<mover accent="true">1¯</mover>2}</semantics> twinning boundaries, but possessing an almost identical texture characteristic, were prepared by pre-compression perpendicular to the extrusion direction. Subsequently, these pre-strained samples were tensioned along the extrusion direction. The results indicate that the pre-induced <semantics>{10<mover accent="true">1¯</mover>2}</semantics> twinning boundaries can indeed enhance the tension strength of magnesium alloys, but only slightly. The effect is closely associated with the amount of pre-strain. Correspondingly, the possible mechanisms behind such phenomena are given and discussed.